PENGARUH AKTIFITAS SISWA DALAM PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS IX SMP NEGERI 2 KOTA PROBOLINGGO - Anik Sulastri (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2016)
This research aims to know influence students activity in learning process to learning achievement, influence of learning motivation to learning achievement, and influence of students activity in learning process and learning motivation by together to learning achievement of IX grader Junior High School 2 Probolinggo. Sixty (60) random students are invoked randomly as the respondents. The results show that there is influence students activity in learning process to learning achievement, learning motivation to learning achievement and influence of students activity in learning process and learning motivation by together to learning achievement of IX grader Junior High School 2 Probolinggo.